Science Objectives for Flagship-Class Mission Concepts for the Search for Evidence of Life at Enceladus - MacKenzie, Shannon M.; Neveu, Marc F.; Davila, Alfonso F.; Lunine, Jonathan; Cable, Morgan L.; Phillips-Lander, Charity M.; Eigenbrode, Jennifer L.; Waite, J. Hunter Jr.; Craft, Kathleen L.; Hofgartner, Jason D.; McKay, Christopher P.; Burton, Dana; et al. (Astrobiology, 2022)
Cassini revealed that Saturn’s Moon Enceladus hosts a subsurface ocean that meets the accepted criteria for habitability with bio-essential elements and compounds, liquid water, and energy sources available in the environment. Whether these conditions are sufficiently abundant and collocated to support life remains unknown and cannot be determined from Cassini data. However, thanks to the plume of oceanic material emanating from Enceladus’ south pole, a new mission to Enceladus could search for evidence of life without having to descend through kilometers of ice. In this article, we outline the science motivations for such a successor to Cassini, choosing the primary science goal to be determining whether Enceladus is inhabited and assuming a resource level equivalent to NASA’s Flagship-class missions. We selected a set of potential biosignature measurements that are complementary and orthogonal to build a robust case for any life detection result. This result would be further informed by quantifications of the habitability of the environment through geochemical and geophysical investigations into the ocean and ice shell crust. This study demonstrates that Enceladus’ plume offers an unparalleled opportunity for in situ exploration of an Ocean World and that the planetary science and astrobiology community is well equipped to take full advantage of it in the coming decades.